2015
DOI: 10.7903/ijecs.1391
|View full text |Cite
|
Sign up to set email alerts
|

Social Support on Facebook: The Influence of Tie Strength and Gender Differences

Abstract: How do people define their online relationships? Do "friends" still offer social support to each other on Facebook? This article discusses the effects of tie strength and gender difference on social support for online friendships. The results showed that individuals with strong ties have a significantly higher frequency of clicking "like," and posting comments and messages on Facebook than individuals with weak ties do. In addition, females have a significantly higher frequency of liking, commenting and messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The study also examined if there are differences in models in relation to the gender of individuals. In particular, taking into account previous research, 11,12,13,14 the research question focused on gender differences for PFU and PVG predictors. Additionally, another aim of the study was to examine the relationship between both types of problematic behaviors taking into account objective variables such as the frequency and duration of use, which has been identified as predictors of problematic behavior in previous studies.…”
Section: Diagnostic and Statistical Manual Of Mental Disorders (Dsm-5) In Section III (Condition Formentioning
confidence: 99%
“…The study also examined if there are differences in models in relation to the gender of individuals. In particular, taking into account previous research, 11,12,13,14 the research question focused on gender differences for PFU and PVG predictors. Additionally, another aim of the study was to examine the relationship between both types of problematic behaviors taking into account objective variables such as the frequency and duration of use, which has been identified as predictors of problematic behavior in previous studies.…”
Section: Diagnostic and Statistical Manual Of Mental Disorders (Dsm-5) In Section III (Condition Formentioning
confidence: 99%
“…Previous studies have suggested that online consumers who take part in a variety of social interaction activities are most likely to follow through with their intention to make a purchase. However, most of these studies have focused exclusively either on the design features of social commerce issues (e.g., Curty & Zhang, 2013;Hajli, 2015;Huang & Benyoucef, 2013;Wang & Zhang, 2012) or social influence issues (e.g., Hajli, 2014;Hsiao & Wang, 2015;Liang et al, 2011;Luarn, Kuo, Chiu, & Chang, 2015; as they seek to understand how consumers interact with each other through Web 2.0 technologies in social commerce environments. As yet, the role of social interaction still remains vaguely understood, and the link between social interaction and consumer intention and behavior has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…For the research about interactive frequency, Ahmed, Villata and Governatori [26] studied the attitudes of individuals in the social networks to privacy issues, and proposed information and friend isolation strategies based on the frequency of interaction between individuals and the sensitivity of information. Luarn et al [27] discussed the effects of relationship strength and gender difference on social support for online friendships, and showed that individuals with strong relationships had a significantly higher frequency of clicking like, and posting comments and messages on Facebook than individuals with weak relationships did. Jason et al [28] found the frequency of online interaction was diagnostic of a strong relationship, and it was a much more useful diagnostician than the attributes of the user or the user's friends.…”
Section: Literature Reviewmentioning
confidence: 99%